Potensi Air Perasan Kunyit Putih, Kunyit Kuning Dan Kunyit Hitam Terhadap Bakteri Escherichia coli Penyebab Diare - Sari, Emilda; Suwandi, Edy; Triana, Linda; Nurhidayattulloh, Ariffialdi (Jurnal Laboratorium Khatulistiwa, 2024)
Turmeric is a herbal plant that is widely used by the public (Curcuma domestica Val) which is proven to contain ingredients that can function as an antibacterial. The antibacterial properties of turmeric rhizomes are caused by its main chemical content, namely curcuminoids and essential oils. Other active substances in turmeric that can be used as antibacterials are flavonoids, alkaloids and tannins. This compound functions as an antibacterial.This research aims to explain the differences in the inhibitory power of White Turmeric, Yellow Turmeric and Black Turmeric juice against Escherichia coli bacteria. The research design used was quasi-experimental. The samples in this study were the juice of White Turmeric, Yellow Turmeric and Black Turmeric which was repeated 10 times for each treatment.Based on the research results, it is known that white turmeric rhizome juice has an average barrier potential of 33.7 mm against Escherichia coli bacteria. This is no different from the juice of Yellow Turmeric rhizomes which has an average barrier potential of 32.7 mm against Escherichia coli bacteria. Meanwhile, the juice from Black Turmeric has a smaller potential resistance compared to the juice from the rhizomes of White Turmeric and Yellow Turmeric, namely an average of 26.2 mm.